Förenkla och förbättra, i vilket avseende? - En analys av de föreslagna beräkningsreglerna och det justerade närståendebegreppet i SOU 2024:36. - Iderstam,Christian (2025)
The special rules for the taxation of dividends and capital gains on qualified shares, also known as the 3:12-framework have since its introduction been regarded as a particularly complex area of Swedish tax legislation. With the aim to both simplify and improve the regulatory framework for shareholders of qualified shares, ”Kommittén om förenklad beskattning av ägare till få-mansföretag” presented the committee report Förenkla och förbättra (SOU 2024:36). This thesis addresses two central aspects of the committee report; the proposed legislative changes regarding the general calculation rules and the concept of related parties within the applicability of the 3:12-framework. The thesis begins with a selective summary of the historical background and the development of the 3:12-framework. This is done to introduce the legal considerations that have shaped today’s legislation and to highlight the origi-nal purpose of the rules. Following this, relevant parts of the current framework is presented before the proposals in the committee report are out-lined. With both applicable law and the committee’s proposal presented, the thesis then introduces 18 examples illustrating the potential effects that may arise if the legislative proposals are adopted in full. These are analyzed from the per-spective of four different key groups within the 3:12-regulatory framework: single-owned companies, companies with a large payroll, key individuals and family-owned businesses. The outcomes of applying these examples under current law are then compared to the outcomes when applying the same ex-amples under the proposed. Based on this analysis, certain conclusions are drawn that in part support the committee’s proposals, while also questioning certain aspects of the proposal. Regarding the proposed changes to the calculation rules, the final reflections and concluding analysis shows that shareholders who have not previously applied ”huvudregeln” in its entirety are likely to benefit which is in line with the committee’s stated purpose. However, whether some of the proposed changes truly benefits the suggested parties according to the committe, or if it is in fact the largest closely held companies which can expect an improvement rather than small and medium-sized enterprises is questioned. Regarding the suggested changes to the meaning of related parties, the final reflections con-cludes that the proposal in some aspects may simplify the 3:12-frame work for siblings. Especially those whose tax-situation would no longer be in-fluenced by their siblings. Furthermore, family-owned companies who want to exit the 3:12-framework may now be able to do so more efficiently. Ho-wever, the analysis also questions the committee’s arguments for the sugges-ted changes, and that potential effects if the proposals are implemented argua-bly require a more solid foundation than presented.
Keywords: skatterätt; fåmansföretag; SOU 2024:36; 3:12